Kabeljaukrise in der Nordsee erfordert neue bestandserhaltende Maßnahmen - Rätz, Hans-Joachim (2003)
The European Commission has claimed a fundamental revision of the European Common Fisheries Policy in its Green Paper (EC 2001) by highlighting the reasons of continued overfishing of a number of valuable demersal fish stocks. Quotas in excess of scientific recommendations, fleet over capacities and poor enforcement of management decisions were identified causal for major stock and yield reductions while gaps in scientific advices were also criticized. The depleted cod stock in the North Sea, Skagerrak and Eastern Channel is the most prominent example. Existing and proposed management regulations were analysed by an expert group which met with fishing industry consultations in Brussels during 28 April – 7 May 2003. Depending on compliance with new technical regulations since 2000, the cod stock and its exploitation was found only marginally effected, while whiting displayed immediately significant losses in yield over long term and short term losses in haddock yields were reversed in substantial gains, also in SSB. However, reduction in fishing effort was found more effective in recovery potential than technical changes including closed areas, for which detailed information about variation in distribution of the stocks and the fisheries are required. Such effort reductions would reduce not only landings but also unregulated discarding, which is believed to be a major reason of the failure of the management measures in mixed fisheries. Recent trends in fishing effort of European fleets could not be quantified due to persistent data deficiencies. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.